NUMERICAL SOLUTION OF TWO DIMENSIONAL COUPLED SHALLOW WATER - EXNER EQUATIONS - Jonathan, Gabriel
To simulate a coastal morphodynamics events on two-dimensional basins, a solution to the two-dimensional coupled shallow water - Exner equations is presented. The governing equations consisted of the shallow water equations for hydrodynamics, and the Exner equation for morphodynamics. A finite volume method on staggered grids was implemented to solve the coupled equations. The proposed numerical scheme is able to simulate various two-dimensional sediment transport problems. To evaluate the performance of the model, various simulation results were presented, alongside its analytical solution or experimental data for comparison.